Self-Reflection Strategy Based on Spiritual Journals in Improving Students' Religious Attitudes in Islamic Religious Education Learning - Restu Rizki Amanda; Munawar Rahmat; Mohamad Rindu Fajar Islamy (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This study aims to analyze the implementation of self-reflection strategies through spiritual journals in Islamic Religious Education (PAI) learning and examine its effect on improving students' religious attitudes. The study used a mixed-methods approach with a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted over two cycles. The research subjects consisted of 26 grade X students at SMA YWKA Bandung. Data were collected through observation, spiritual journals, interviews, religious attitude questionnaires, and documentation, and then analyzed using the Miles and Huberman interactive model, descriptive statistics, and a paired-samples t-test. The results showed that implementing spiritual journals significantly improved students' religious attitudes, as evidenced by an increase in indicator achievement from 50% at the beginning of the cycle to 100% at the end of cycle II. Quantitatively, the average score of religious attitudes increased from 129.35 to 137.73, with t-test results indicating a significant difference (p < 0.05) and an effect size of 0.74 (medium-large category). Qualitatively, student reflection progressed from a descriptive stage to analytical and personal reflection, indicating increased self-awareness and internalization of religious values. These findings confirm that spiritual journals can serve as reflective learning strategies to strengthen students' affective, spiritual, and moral dimensions and to bridge the gap between religious understanding and daily life practices.